RETRACTED: Paeonol Suppresses Proliferation and Motility of Non-Small-Cell Lung Cancer Cells by Disrupting STAT3/NF-κB Signaling - Zhang, Lei; Chen, Wen-Xu; Li, Ling-Li; Cao, Yu-Zhu; Geng, Ya-Di; Feng, Xiao-Jun; Wang, Ai-Yun; Chen, Zhao-Lin; Lu, Yin; Shen, Ai-Zong (Frontiers in Pharmacology, 2020)
Background: Targeting inflammatory microenvironment is a promising anti-tumor strategy. Paeonol is a phenolic compound with effective anti-inflammatory and anti-tumor properties. However, the effects of paeonol on non-small cell carcinoma (NSCLC) have not been fully inevestogated. Here, we evaluated the effects of paeonol on proliferation and metastasis of NSCLC and ecludated the underlying mechanisms. Methods: The effects of paeonol on inflammatory cytokines were determined by cell proliferation and ELISA assays. Assays of wound healing, single cell migration and perforation invasion were used to evaluate migration and invasion of NSCLC cells. Expression of marker proteins in epithelial-mesenchymal transition and matrix metalloproteinase family enzymes was detected by Western blot assays. Nude mouse A549 cells transplantation tumor model was used to study the anti-lung cancer effects of paeonol in vivo. TUNEL stanining was used to detect the apoptosis of tumor cells in A549 lung cancer mice, and Ki67 analysis was used to detect the proliferation of tumor cells in A549 lung cancer mice. Immunohistochemistry was used to detect the effects of paeonol on signaling molecules in tumor tissues. Results: Paeonol inhibited A549 cancer cell migration and invasion in vitro. Paeonol inhibited secreaion of inflammatory cytokines in A549 cells, including tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-1β, and transforming growth factor (TGF)-β. Paeonol altered the expression of marker proteins involved in epithelial-mesenchymal transition and matrix metalloproteinase family enzymes. In addition, paeonol inhibited the transcriptional activity of NF-κB and STAT3 phosphorylation. Paeonol inhibited the growth of A549 cells transplanted tumors in nude mice. Conclusion: Paeonol potently inhibited NSCLC cell growth, migration and invasion associated with disruption of STAT3 and NF-κB pathways and could be a promising anti-metastatic candidate for tumor chemotherapy.